Utility of autologous fibrin glue and polyglycolic acid sheet for preventing delayed bleeding associated with antithrombotic therapy after gastric ESD - Kikuchi, Daisuke; Iizuka, Toshiro; Makino, Shigeyoshi; Hayasaka, Junnosuke; Odagiri, Hiroyuki; Ochiai, Yorinari; Suzuki, Yugo; Nomura, Kosuke; Ohkura, Yu; Okamoto, Yosuke; Tanaka, Masami; Matsui, Akira; Mitani, Toshifumi; Hoteya, Shu (Endoscopy International Open, 2019)
Background and study aims Delayed bleeding is one of the most serious adverse events of gastric endoscopic submucosal dissection (ESD), especially in patients taking antithrombotic therapy. This study aimed to evaluate the utility and safety of a shielding method with autologous fibrin glue and polyglycolic acid (PGA) sheets for patients undergoing gastric ESD who are receiving antithrombotic therapy.Patients and methods One hundred twenty-three patients who were treated with gastric ESD while receiving antithrombotic therapy between December 2014 and September 2017 were enrolled in this study. Patients who received the shielding method were classified into the shielding group. Others were classified into the conventional group. Various clinico-pathological factors were retrospectively compared between the two groups. Results The shielding group consisted of 38 patients, and the conventional group consisted of the remaining 85 patients. In the shielding group, the rate of continuation of antithrombotic therapy was significantly higher (68.4 % vs 41.2 %). Incidence of delayed bleeding was lower in the shielding group (2.6 %, 1/38) than in the conventional group (14.1 %, 12/85). In the propensity score-adjusted logistic regression analysis, the delayed bleeding rate in the shielding group tended to be lower than in the conventional group (P = 0.070). Allogeneic transfusion was performed in eight patients (8/85, 9.4 %) in the conventional group and none in the shielding group (P = 0.047). No adverse event associated with endoscopic shielding were observed in the shielding group.Conclusions This study suggests that a shielding method with autologous fibrin glue and PGA sheet effectively prevents delayed bleeding after gastric ESD in patients receiving antithrombotic therapy.